A novel electromechanical autoinjector, AutoTouch™, for self-injection of etanercept: real-world use and benefits. Issue 1 (2nd January 2017) - Collier, David H.; Bitman, Bojena; Coles, Andrew; Liu, Lyrica; Kumar, Sandeep; Judd, Clinton
ABSTRACT: Objectives: We assessed the ability of patients with autoimmune inflammatory diseases to successfully use the investigational AutoTouch™ reusable autoinjector as well as patient preference for AutoTouch™ versus the currently marketed single-use prefilled etanercept SureClick® autoinjector. Methods: Two multicenter studies were performed: a Home Use Study and a Patient Preference Study. In the Home Use Study, 77 patients with rheumatoid arthritis (RA) or psoriatic arthritis self-administered etanercept once weekly for 5 weeks. The primary end point was successful self-injection of etanercept via AutoTouch™. The Patient Preference Study was an open-label, randomized, 8-week crossover trial (4 weeks for each device) in 216 patients with RA or psoriasis (PsO). The primary end point was preference for AutoTouch™ versus SureClick®. Results: In the Home Use Study, the proportion of successful self-injections with AutoTouch™ during weeks 1 through 5 was 97.8% (95% CI, 96.3‒99.3). In the Patient Preference Study, patients had a preference rate for AutoTouch™ of 41.7% (95% CI, 34.9–48.4) overall, 43.5% (95% CI, 35.5‒51.6) for patients with RA, and 36.8% (95% CI, 24.3‒49.4) for patients with PsO. Needle apprehension was not different at initiation of the autoinjectors, nor was there a difference between the injectors after 4 weeks. Overall, patients preferred AutoTouch™ for ease of self-injecting, ease of pressing the start button, ease of following injection progress, and certainty of knowing when the injection was completed. SureClick® was preferred for fewer steps and experiencing less injection site discomfort or pain. Conclusion: The introduction of the AutoTouch™ will give patients a choice between two different autoinjectors for self-administration of etanercept.